A study of highly activated hydrogen evolution reaction performance in acidic media by 2D heterostructure of N and S doped graphene on MoOx - Kubra Aydin; Seongwon Woo; Vinit Kaluram Kanade; Seulgi Choi; Chisung Ahn; Byungkwon Lim; Taesung Kim (Carbon Energy, 2023)
Abstract Herein, a layer of molybdenum oxide (MoOx), a transition metal oxide (TMO), which has outstanding catalytic properties in combination with a carbon‐based thin film, is modified to improve the hydrogen production performance and protect the MoOx in acidic media. A thin film of graphene is transferred onto the MoOx layer, after which the graphene structure is doped with N and S atoms at room temperature using a plasma doping method to modify the electronic structure and intrinsic properties of the material. The oxygen functional groups in graphene increase the interfacial interactions and electrical contacts between graphene and MoOx. The appearance of surface defects such as oxygen vacancies can result in vacancies in MoOx. This improves the electrical conductivity and electrochemically accessible surface area. Increasing the number of defects in graphene by adding dopants can significantly affect the chemical reaction at the interfaces and improve the electrochemical performance. These defects in graphene play a crucial role in the adsorption of H+ ions on the graphene surface and their transport to the MoOx layer underneath. This enables MoOx to participate in the reaction with the doped graphene. N‐ and S‐doped graphene (NSGr) on MoOx is active in acidic media and performs well in terms of hydrogen production. The initial overpotential value of 359 mV for the current density of −10 mA/cm2 is lowered to 228 mV after activation.